Expansion rate of descending thoracic aortic aneurysms. Issue 13 (17th October 2016) - Patterson, B. O.; Sobocinski, J.; Karthikesalingam, A.; Hinchliffe, R. J.; Loftus, I.; Thompson, M. M.; Holt, P. J.
Abstract: Background: Surveillance is mandatory for all patients with a thoracic aortic aneurysm (TAA). The frequency of surveillance imaging, however, is not evidence‐based, as few data exist regarding TAA growth rates. This study aimed to determine the rate of TAA expansion and to inform surveillance intervals based on TAA diameter. Methods: Patients with a TAA for whom morphological data were available from serial CT scans were studied. Annualized growth rates based on diameter at presentation and time taken to reach a theoretical intervention threshold of 55 mm were calculated. The number of patients who would have achieved the threshold undetected was determined based on simulated imaging intervals of 6 months, 1, 2 and 3 years. Results: A total of 2916 scans from 995 patients were analysed. The mean aortic expansion rate was 2·76 mm per year for all patients, with an exponential increase observed at sizes above 45 mm. Only 3·9 per cent of patients with a starting diameter of 30–39 mm and 5·3 per cent of those with a diameter of 40–44 mm achieved threshold size within 2 years. Conversely, the probability of expansion to more than 55 mm was 74·5 per cent in 2 years for patients with a starting diameter of 50–54 mm, rising to 85·7 per cent at 3 years. Conclusion: Based on a threshold of 55 mm for intervention, most patients with a maximum aortic diameter below 40 mm could safely undergo surveillance at 2‐yearly intervals. Above 45 mm, annual surveillance is recommended. Patients with a diameter greater than 50 mm could be optimized for possible repair, if this is clinically appropriate. Abstract : Surveillance intervals proposed